LEARNING THROUGH A REALISTIC MATHEMATICS EDUCATION APPROACH TOWARDS CRITICAL THINKING AND LOGICAL INTELLIGENCE - Hanizyah Quswatul Khasanah; Darsono Darsono; Dian Devita (Universitas Muhammadiyah Lampung, 2026)
This study aims to analyze the effectiveness of the Realistic Mathematics Education (RME) approach on students' critical thinking skills and logical mathematical intelligence in the material of quadratic equations and functions. The background of this study is the low level of both abilities due to teacher-centered learning and the lack of active student involvement, especially in abstract quadratic material. RME was chosen because it emphasizes real contexts and mathematization processes that are believed to develop students' thinking skills. This study used a quasi-experimental method with a posttest-only control group design. The subjects were grade X students of SMAN 1 Gurah who were divided into experimental and control classes. The research instruments were 5 essay questions to measure critical thinking and 15 multiple-choice questions for logical mathematical intelligence that were valid and reliable. Data were analyzed using descriptive and inferential statistics through linear regression tests. The results showed that the implementation of RME learning was very good with a score of 3.67. The average critical thinking score of the experimental class (41.35) was higher than that of the control class (25.59), while the logical mathematical intelligence of the control class (41.91) was slightly higher than that of the experiment class (41.18). Regression tests showed a significant effect of RME, with a negative effect on critical thinking and a positive effect on logical-mathematical intelligence. Consequently, RME needs to be combined with strategies that explicitly train critical thinking to ensure balanced development of both abilities